A new cavernicolous assassin bug from the Canary Islands (Hemiptera: Reduviidae: Emesinae: Collartidini) - Davranoglou, Leonidas-Romanos; Baňař, Petr; Suárez, Daniel; Martín, Sonia; Naranjo, Manuel (Zootaxa, 2022)
The Canary Archipelago is home to two species of obligately cavernicolous assassin bugs of the genus Collartida Villiers, 1949 (Hemiptera: Heteroptera: Reduviidae: Emesinae: Collartidini). These species are highly adapted for cave life, being blind and wingless. In the present study, we describe a new species of the genus, C. phantasma sp. nov. from the Federica mine in Gran Canaria. C. phantasma sp. nov. differs from the other two Collartida species found in the Canary Archipelago in that the male is fully winged, the female is wingless, and both sexes have well-developed eyes. We provide information regarding the new species’ habitat, its taxonomic affinities, and its ability to fly.